The role of interoception in the overlap between eating disorders and autism: methodological considerations - Adams, K; Murphy, J; Catmur, C; Bird, G (Wiley, 2022)
Significant comorbidity has been demonstrated between feeding and eating disorders and autism. Atypical interoception (perception of bodily signals) may, at least in part, be responsible for this association, as it has been implicated in the aetiology of both conditions. However, significant methodological limitations are impeding progress in this area. This paper provides a brief overview of how interoception has been linked to autism and feeding and eating disorders in both adolescent and adult populations before identifying several issues with current measures of interoception. We suggest that methodological issues may be contributing to the inconsistency in the empirical literature, and provide suggestions for future research.